Difference in Risk Factors for Breast Cancer by ER Status in an Indigenous African Population. (25th June 2013) - Galukande, M.; Wabinga, H.; Mirembe, F.; Karamagi, C.; Asea, A.
Abstract : Introduction . Breast cancer is the commonest cancer among women globally. In Uganda, it is on the rise, projected at a 4.5% annual ASR increase (age standardized incidence rate). The reasons for this steep increase are not fully established. In the recent past, gene profiling in tumor tissues suggests that breast cancers are divided into subtypes dependent on the presence or absence of oestrogen receptor, progesterone, and human epidermal growth factor receptor 2 (HER 2). These subtypes do have distinctive clinical outcomes and perhaps risk factors from past studies. There is paucity of data on hormonal receptor status and the traditionally known risk factors in sub-Saharan Africa. The purpose of this study therefore was to establish the differences between ER status and the traditionally known risk factors for breast cancer in Uganda. Methods . An observational analytical hospital, based study, carried out at Makerere University, College of Health Sciences. Formalin fixed and paraffin imbedded sections were prepared for haemotoxylin and eosin (H&E) stains and immunohistochemistry (IHC). Ethical approval was obtained. Results . A total of 113 women were recruited. Mean age was 45 years (SD14). There were no significant differences in selected risk factors (setting, age, contraceptive use, parity, breast feeding, or menarche) by ER status although ER negative tumors had significantly higher grade tumors (by a factor of two) compared to ER positive tumors. Conclusion . There were no significant differences among risk factors by ER status contrary to what several other studies suggest. The manifestation of breast cancer in Africa warrants further extensive inquiry.